Bagaimana Transformational Leadership Memfasilitasi Work Innovation: Peran mediasi Knowledge Management - Muzakki, Muzakki; Christina, Christina (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
This study aims to explore the effect of transformational leadership on work innovation and knowledge management, as well as the mediating role of knowledge management in the relationship between transformational leadership and work innovation. The research method used is quantitative research, with the use of partial least square (PLS) analysis techniques. The findings of this study reveal that transformational leadership has a positive and significant effect on work innovation directly. Transformational leadership also has a positive and significant impact on knowledge management. Then knowledge management plays a role as mediation in the relationship between transformational leadership and work innovation in a positive and significant manner in this study.